2021
DOI: 10.1088/1873-7005/ac12af
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic waves as control actuator for drop removal from solid surface

Abstract: Several types of research are performed on flow control and this fact highlights the importance of this topic. Over the last two decades, actuators based on acoustic waves have attracted much attention and have been used in widespread applications from mixing to pumping. This paper reveals the effects of some control parameters such as wave amplitude and wave frequency on the dynamical behavior of a sessile drop in order to change the flow characteristics. For this purpose, the removal of water from surfaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Noori et al [ 62 , 63 , 64 , 65 ] utilized a multiple-relaxation-time color-gradient model lattice Boltzmann method to establish a two-dimensional (2D) model for the interaction between droplets and SAWs ( Figure 3 a–c). By introducing a contact angle hysteresis model, the numerical accuracy was improved by 20% [ 62 ].…”
Section: Fundamentals Of Adementioning
confidence: 99%
See 1 more Smart Citation
“…Noori et al [ 62 , 63 , 64 , 65 ] utilized a multiple-relaxation-time color-gradient model lattice Boltzmann method to establish a two-dimensional (2D) model for the interaction between droplets and SAWs ( Figure 3 a–c). By introducing a contact angle hysteresis model, the numerical accuracy was improved by 20% [ 62 ].…”
Section: Fundamentals Of Adementioning
confidence: 99%
“…Additionally, LBM simulation results showed that viscosity reduction, hydrophobicity, and surface tension coefficient increase significantly affected the flow and jetting control system and increased its sensitivity [ 64 ]. The dynamic behavior of droplets under microgravity conditions was affected by the Bond number with droplets able to move vertically on the surface when the Bond number exceeded a critical value [ 65 ]. Regarding drop removal using surface acoustic waves on a flat surface, LBM simulation results showed that the contact time was reduced by three times when a pair of SAWs with the same amplitude and frequency were applied [ 66 ].…”
Section: Fundamentals Of Adementioning
confidence: 99%
“…Surface acoustic waves have been utilized to manipulate water droplets on solid surfaces (Sheikholeslam Noori et al, 2020a;Sheikholeslam Noori et al, 2020b;Noori et al, 2020;Sheikholeslam Noori et al, 2021). They have been proposed as a potential technique to prevent water droplet icing on aircraft wings in areas not covered by the anti-ice system (Taeibi Rahni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Active flow control involves the use of external energy sources or actuators to actively manipulate the flow field in real time. They involve active adjustment of control parameters to achieve the desired flow modification, such as modulated pulse jets Abdolahipour et al (2022b), Abdolahipour et al (2022a), Abdolahipour et al (2021), Abdolahipour (2023), plasma actuators Taleghani et al (2018), and the generation of surface waves Noori et al (2021) Rahni et al (2022 and magnetic field Azadi et al (2023). Passive flow control, on the contrary, relies on the inherent properties of flow-obstructing devices or passive structures to modify the flow behavior without requiring external energy input.…”
Section: Introductionmentioning
confidence: 99%